2020
DOI: 10.1007/s42452-020-03481-9
|View full text |Cite
|
Sign up to set email alerts
|

Maximum dry density of sand–kaolin mixtures predicted by using fine content and specific gravity

Abstract: Numerous studies have covered the comparison of maximum dry density (MDD) toward the combination of soil properties and compaction parameters. These combinations are dominated by Atterberg limits, moisture content, and compaction effort. Nevertheless, minimal efforts have been expended in predicting the MDD using two simple soil properties, i.e., fine content (FC) and specific gravity (G s ). Sand-kaolin mixtures were compacted and then used to examine the correlation between MDD, FC, and G s through different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This is because if the distillation is carried out at high temperatures, then the amount of water accompanying the alcohol will also be more and vice versa so that the density of the distillate will also be high. As is known, specific gravity is the ratio between the specific gravity of alcohol and the specific gravity of water at the same temperature (Alshameri, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This is because if the distillation is carried out at high temperatures, then the amount of water accompanying the alcohol will also be more and vice versa so that the density of the distillate will also be high. As is known, specific gravity is the ratio between the specific gravity of alcohol and the specific gravity of water at the same temperature (Alshameri, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In Alshameri's [19] experiment, he used a mixture of sand and kaolin at different percentages. In his study, a mixture of 80% sand and 20% kaolin yielded the highest dry density, with an OMC of 12%.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that an increment in C F correspondingly results in a diminished ρ dmax , while concurrently elevating the w opt . In another study, sand-kaolin blends were compressed to investigate the connection between ρ dmax , C F , and specific gravity (Gs) across different moisture levels, with C F ranging from 20% to 70% [66]. A prominent linear correlation (R 2 = 0.99) was found between ρ dmax and the C F /Gs 2 ratio.…”
mentioning
confidence: 99%